2019
DOI: 10.17159/0379-4350/2019/v72a4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Silver Nanoparticles, Sucrose and Sodium Chloride as Osmotic Solutions for Tomato Slices: Antioxidant Activity, Microbial Quality and Modelling with Polynomial Regression Model

Abstract: This study has reported comparative effects of silver nanoparticles (AgNPs), sucrose and sodium chloride as osmotic solutions on antioxidant activity and microbial quality of 10 mm tomato slices. 40 g of tomato slices were dehydrated osmotically (OD) at different temperatures (60, 70 and 80°C) and time (30, 60, 90, 120 150 and 180 min). Water loss, solid impregnation, water and solid diffusivities of tomato slices were found to increase with increase in solution temperatures and concentrations with AgNPs havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…In several studies, it has been shown that biosynthesized AgNPs can modulate treated plants to improve their antioxidant activities. Corchorus olitorius grown with different levels of AgNPs increased the DPPH scavenging and ferric reducing abilities of the leaf extract by 1.8 and 4.94 fold respectively(Azeez et al, 2019a) Azeez et al (2019b). also showed that cocoa-bean mediated AgNPs can be used for osmotic dehydration of tomato slices with improved microbial quality and antioxidant properties.…”
mentioning
confidence: 79%
“…In several studies, it has been shown that biosynthesized AgNPs can modulate treated plants to improve their antioxidant activities. Corchorus olitorius grown with different levels of AgNPs increased the DPPH scavenging and ferric reducing abilities of the leaf extract by 1.8 and 4.94 fold respectively(Azeez et al, 2019a) Azeez et al (2019b). also showed that cocoa-bean mediated AgNPs can be used for osmotic dehydration of tomato slices with improved microbial quality and antioxidant properties.…”
mentioning
confidence: 79%
“…Yu et al ( 27 ) observed the growth of bacteria, yeast, and fungi in osmotically dehydrated blueberries. In addition, Azeez et al ( 28 ) found viable fungi in osmotically dehydrated tomato slices. These indigenous microbiotas, which are usually found on the fruit surface, become the main initiator of spontaneous fermentation because of their adaptive nature to the mango matrix ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metal nanoparticles can be used as nanofertilisers supplying essential minerals or be applied to improve the performance of conventional chemical fertilisers. They are more efficient in supplying nutrients and contribute lesser environmental pollution because of their controllable rates of release thereby reducing the risk of nutrient run-off into water [3,5,[11][12][13][14][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%